Roll‐to‐Roll Dyed Conducting Silk Yarns: A Versatile Material for E‐Textile Devices. Issue 12 (10th September 2018) - Lund, Anja; Darabi, Sozan; Hultmark, Sandra; Ryan, Jason D.; Andersson, Barbro; Ström, Anna; Müller, Christian
Abstract: Textiles are a promising base material for flexible and wearable electronic applications such as sensors, actuators, and energy harvesters. An essential component in such electronic textiles (e‐textiles) is electrically conducting yarns. Here, a continuous dyeing process is presented to convert an off‐the‐shelf silk sewing thread into a wash and wear resistant functional thread with a conductivity of about 70 S cm −1 ; a record high value for coated yarns. An aqueous ink based on the conducting polymer:polyelectrolyte complex poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is modified, to produce more than 100 m of dyed conducting threads, which are subsequently converted into e‐textiles by both hand weaving and machine embroidery. The yarns are resistant to abrasion and wear, and can be machine washed at least 15 times with retained electronic properties. The woven fabric is used to design a capacitive touch sensor which functions as an e‐textile keyboard. Abstract : A textile keyboard, and a range of other electronic textiles (e‐textiles) can be manufactured by traditional techniques including weaving, knitting and stitching. Here, a roll‐to‐roll dyeing process to continuously produce electrically conducting yarns—a basic building block in e‐textiles—is presented. The threads are wash and wear resistant, and have a conductivity of 70 S cm ‐1 .